Bishops on the Chair of Pestilence: Ambrosiaster's Polemical Exegesis of Psalm 1.1 - Lunn-Rockliffe, Sophie (Journal of early Christian studies, 2011)
This article examines Ambrosiaster's exegesis of Psalm 1 in his quaestio 110, focusing on his strikingly lengthy explanation of the cathedra pestilentiae of Ps 1.1. It locates his interpretation of the cathedra pestilentiae in a particular tradition of Latin anti-heretical scriptural allusion: Cyprian's polemic against rigorists and Optatus of Milevis's denunciation of Donatist antibishops. This illuminates the likely target of this passage as the Donatist antibishop of Rome in the late 370s, Claudian. However, the connections between q. 110 and other quaestiones suggest that Ambrosiaster may also have had the Novatianists in his sights.